2010
DOI: 10.1111/j.1440-169x.2009.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Chicken embryonic stem cells as a non‐mammalian embryonic stem cell model

Abstract: Embryonic stem cells (ESCs) were isolated in the early 1980s from mouse and in the late 1990s from primate and human. These cells present the unique property of self-renewal and the ability to generate differentiated progeny in all embryonic lineages both in vitro and in vivo. The mESCs (mouse embryonic stem cells) can contribute to both somatic and germinal lineages once re-injected into a recipient embryo at the blastocyst stage. In avian species, chicken embryonic stem cells (cESCs) have been isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 87 publications
(163 reference statements)
0
30
0
Order By: Relevance
“…Cells from the blastoderm of EGK-X stage chick embryos have been isolated and maintained in culture, and shown to contribute to chimeric embryos, and in some cases to the germ line. 30,49 Our results do not contradict the possibility that these cells are genuine multipotent cells, as they could be derivatives of PGCs (as we have argued before; Fernandez-Tresguerres et al 2010), or might even represent a cell type more akin to EpiS cells. 50,51 This would explain both the expression of the chick homologs of Oct4 and Nanog, and the particular growth factor requirements of these cells in culture (for example, the need for Fgfs).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 35%
“…Cells from the blastoderm of EGK-X stage chick embryos have been isolated and maintained in culture, and shown to contribute to chimeric embryos, and in some cases to the germ line. 30,49 Our results do not contradict the possibility that these cells are genuine multipotent cells, as they could be derivatives of PGCs (as we have argued before; Fernandez-Tresguerres et al 2010), or might even represent a cell type more akin to EpiS cells. 50,51 This would explain both the expression of the chick homologs of Oct4 and Nanog, and the particular growth factor requirements of these cells in culture (for example, the need for Fgfs).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 35%
“…It was not determined whether these ciPSCs were present in hatched animals. Reports have regularly shown that cPGCs and cESCs have limited ability to form chimeric animals, with the number of chimeric animals ranging from 3% to 20%, with early passage cells and rates decreasing for late passage cells (Carsience et al, 1993;Lavial and Pain, 2010;Park et al, 2003). Techniques such as magnetic-activated cell sorting (MACS) and FACS based on specific markers, bisulfite treatments, and coring of the zona pellucida have increased chimera generation in chickens (Kim et al, 2010;Song et al, 2005;van de Lavoir et al, 2006b).…”
Section: Discussionmentioning
confidence: 97%
“…Chicken pluripotent stem cell culture conditions have remained elusive, with culture systems only being able to maintain cells for short time periods before changes in plasticity, proliferation, and phenotype of cells occurs (Carsience et al, 1993;Lavial and Pain, 2010;Park et al, 2003). These culture systems are typically complex, even beyond what is used for standard mouse and human pluripotent cells, requiring feeder cells, specialized media, and the use of animal products that have shown significant lotto-lot variability (Chaudhry et al, 2008;Pesce et al, 1993;Shamblott et al, 2001;Turnpenny et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of chicken ESC derivation, it has been possible to develop recombinant chicken LIF (cLIF) which alone with serum was found to be sufficient to maintain chicken ESCs in their undifferentiated state (Horiuchi et al 2004). Despite the ability of cLIF to maintain undifferentiated chicken ESCs, their capacity to contribute successfully to chimeras was not studied yet (Lavial & Pain 2010). More recently, chicken chimeras were obtained by injecting ESCs into the subgerminal cavity of chicken embryos, proving their germline transmission capacity (Zhang et al 2013).…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%